The impact of an educational curriculum using the training method in learning some basic volleyball skills (Journal of the College of Basic Education, 2022)
The researcher used the training method, which is one of (Mosten's) methods, to identify its effect on the learners and to provide appropriate learning opportunities through the optimal investment of effort and time. In this method, some basic volleyball skills were learned for students aged (11) years from Al-Madinah Al-Munawwarah Elementary School.